Optimizing Dye-Sensitized Solar Cell (DSSC) Performance through Synergistic Natural Dye Combinations from Beta vulgaris L., Curcuma longa L., and Pandanus amaryllifolius - Kusumawati, Nita; Setiarso, Pirim; Muslim, Supari; Zakiyah, Nafisatus; Rahmawati, Khofifatul; Fachrirakarsie, Fadlurachman Faizal (Indonesian Journal of Chemistry, 2024)
This study optimizes dye-sensitized solar cell (DSSC) performance using a combination of natural dye components extracted from Beta vulgaris L. (beetroot), Curcuma longa L. (turmeric), and Pandanus amaryllifolius (pandanus leaf). These plants were selected for their natural pigments—betacyanin, curcuminoids, and chlorophyll—which potentially act as DSSC sensitizers. Dyes were extracted via maceration with ethanol solvent (1:6 sample:solvent ratio) for 24 h. Filtrates were combined in various ratios to test DSSC performance. The optimal C4 dye combination, with a 2:1:1 ratio (betacyanin:curcumin:chlorophyll), demonstrated the best performance. The UV-vis analysis revealed complex interactions and synergistic effects among dye combinations, characterized by increased light absorption in the 400–700 nm range. Cyclic voltammetry analysis showed favorable energy band gap values, confirming the pigments' suitability for DSSC applications. FTIR analysis confirmed the stable coexistence of the three dyes without new bond formation. Photovoltaic performance testing showed the C4 three-dye combination achieved the highest energy conversion efficiency of 3.57%. These results demonstrate the potential of this dye combination to contribute to the development of sustainable and efficient solar energy conversion in DSSCs.